2000
DOI: 10.1016/s0886-3350(99)00335-1
|View full text |Cite
|
Sign up to set email alerts
|

AMO array multifocal lens versus monofocal correction in cataract surgery

Abstract: The results of this study indicate high patient satisfaction with the Array multifocal IOL and greater functional independence from spectacle wear, by objective and subjective patient measures, than with the monofocal IOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 9 publications
2
24
0
8
Order By: Relevance
“…No presente estudo, 75% dos pacientes do grupo multifocal tiveram J1 e 100% tiveram AV para perto, melhor ou igual a J3. Enquanto que no grupo monofocal, a AV para perto em 10% foi J1 e 70% até J3, dados concordantes com outros autores na literatura (5)(6)(8)(9) . Apesar da visão para perto de J1, muitos pacientes do grupo multifocal necessitavam de óculos, pois a leitura tornava-se cansativa, principalmente nos pacientes acima de 70 anos.…”
Section: Discussionunclassified
“…No presente estudo, 75% dos pacientes do grupo multifocal tiveram J1 e 100% tiveram AV para perto, melhor ou igual a J3. Enquanto que no grupo monofocal, a AV para perto em 10% foi J1 e 70% até J3, dados concordantes com outros autores na literatura (5)(6)(8)(9) . Apesar da visão para perto de J1, muitos pacientes do grupo multifocal necessitavam de óculos, pois a leitura tornava-se cansativa, principalmente nos pacientes acima de 70 anos.…”
Section: Discussionunclassified
“…Patients reported significant improvements in these symptoms by the 6 th postoperative month, probably due to neural adaptation (10) . Objective and subjective assessments showed that patients with bifocal and multifocal IOLs were more independent from glasses, with a better visual outcome and higher patient satisfaction for far, intermediate and near vision (9,12,13,16,19) . Bifocal IOLs can be a cost-effective alternative for patients in poor financial condition as they reduce the need for glasses after cataract surgery (5) .…”
Section: Resultsmentioning
confidence: 99%
“…A questionnaire (Appendix 1) with 47 questions assessing patient satisfaction, the need for eye glasses, and quality of life was administered to all patients by the same examiner. The questionnaire was developed by combining 3 questionnaires that had been previously validated in a pilot project (5,7,9) All patients underwent surgery in both eyes. All patients provided their Free and Informed Consent, and the study was approved by the Research Ethics Committee (REC) of the Federal University of São Paulo.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5] However, they are known to reduce contrast sensitivity (CS) under low-contrast 6,7 and mesopic conditions, 8 and to induce photic phenomena such as glare and halo with bright light. 5,6,9 In daily life, exposure to different levels of illumination is unavoidable and, although visual acuity is known to improve with increasing illumination, 10 it has not been reported before if, in patients with multifocal IOLs, visual acuity and CS are affected by changing the level of illumination.…”
Section: Introductionmentioning
confidence: 99%